Patient Safety, Service Quality, and Service Excellence as Predictors of Patient Satisfaction: A Study of Student Perceptions at STIKes Widya Husada Tangerang - Irviana, Fitriyati; Saptarani, Yanna Dwi (Asosiasi Dosen Muda Indonesia, 2026)
This study investigates the effects of patient safety, service quality, and service excellence on patient satisfaction from the perspective of students at STIKes Widya Dharma Husada Tangerang. The study is important because student perceptions provide an early indicator of service performance and can inform continuous quality improvement in healthcare facilities. Methodology: A quantitative design was applied using survey data collected through structured questionnaires. The data were analyzed using multiple linear regression, supported by partial t-tests and a simultaneous F-test to examine both individual and joint effects of the independent variables on patient satisfaction. Findings: The results indicate that patient safety has a positive and significant effect on patient satisfaction (t = 2.123; p = 0.038). Service quality also shows a positive and significant effect (t = 3.979; p = 0.032). Service excellence demonstrates a positive and significant influence on patient satisfaction (t = 3.860; p = 0.000). Simultaneously, patient safety, service quality, and service excellence significantly affect patient satisfaction (F = 71.507; p = 0.000), confirming that these factors collectively contribute to improved satisfaction outcomes. Implications: The findings suggest that healthcare providers should implement integrated improvement strategies by strengthening patient safety practices, enhancing service quality dimensions, and institutionalizing service excellence standards to increase patient satisfaction. These results can support managerial decision-making in quality assurance programs and service delivery evaluation. Originality: This study contributes by empirically testing an integrated model that combines patient safety, service quality, and service excellence as simultaneous predictors of patient satisfaction within a student-based perception setting, offering a practical evidence base for targeted service improvement in Indonesian healthcare contexts.